Features dance training athletes «children» (6–9 years) acrobatic rock and roll at an early stage of the first year - Камаєв [Oleg Kamayev], Олег Іванович; Кизим [Petro Kуzim], Петро Миколайович (Slobozhanskyi Herald of Science and Sport, 2013)
<!--[if gte mso 9]> Normal 0 false false false <![endif]--> Reviewed and analyzed the methodology of the training sessions in an acrobatic rock and roll at the initial stage of training athletes the first year. Defined methods of teaching basic dance movements, acrobatic rock 'n' roll. A program and organizational forms of dance training in acrobatic rock 'n' roll for athletes ages 6-9 the first year. The study developed a sequence of learning the basic elements of dance and acrobatic figures of rock 'n' roll at an early stage of preparation. Designed program aimed at improving dance training beginners in an acrobatic rock 'n' roll. The recommendations coaches acrobatic rock and roll on the dance training athletes «Children» (6–9 years) the first year. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->